PEMBULATAN HARGA PADA TRANSAKSI JUAL BELI DI MINIMARKET - Akbar Sabani (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2019)
A new practice in buying and selling that arises when people shop at minimarkets is the practice of rounding off the price of goods by cashiers. This practice of rounding up prices is common in minimarkets such as Indomaret, Alfamart, and Alfamidi. As happened in the minimarket, there was rounding off if the buyer paid the extra money and there was a small change like Rp. 50, - or Rp. 100, -, then the small amount will be rounded off by the cashier. The main problem of the description above is how the review of Islamic economic law regarding rounding prices on buying and selling transactions in the mini market and its impact on consumers. Then in this study using qualitative research methods with an empirical approach and the building of analysis in the article will attempt to articulate several laws related to data reduction, triangulation of the results of articles, and then the presentation of data in the form of narrative text. The data used in this study are secondary in the form of literature, articles, and research journals that have been carried out related to Islamic economic law reviews regarding price rounding on buying and selling transactions at minimarkets and their impact on consumers.